Preemptive Analgesia with Ketorol DT in premolar orthodontic extractions - VT, Indugayathrie; L, Saravanan (Journal of Neonatal Surgery, 2025)
Effective postoperative pain management is crucial in procedures such as dental extractions . Typically, postoperative pain is managed reactively through NSAIDs and opioids. Traditionally analgesics are given post dental extractions. This study evaluates the potential benefits of a preemptive approach of administering Ketorol DT (ketorolac tromethamine) before surgery to minimize postoperative pain, reduce reliance on additional analgesics, and promote faster recovery. Materials and method:Participants were divided into two groups. The control group received standard postoperative pain management with paracetamol and the experimental group received 10 mg of Ketorol DT one hour prior to surgery. Pain was measured using the Visual Analog Scale (VAS) two hours post-surgery. Statistical analyses were conducted using unpaired t-tests with a significance level of p<0.05. Results:This prospective comparative study included 36 patients with mean age of 23.27 ± 3.2 in control group and 21.5± 2.66 in experimental group scheduled for therapeutic premolar orthodontic extractions and in experimental group there was 8 females and 10 males whereas in control group there was 9 males and 9 females. The experimental group receiving Ketorol DT preemptively showed significantly lower pain scores compared to the control group at all time points. The VAS score of of control group was 4.5 ±0.32 the experimental group was 3.7 ± 0.12 with pvalue of 0.024. These reductions in pain scores were statistically significant. Conclusion: Preemptive administration of Ketorol DT effectively reduces postoperative pain following premolar orthodontic extractions, potentially decreasing the need for additional analgesics and improving patient comfort. This approach may provide a valuable alternative to reactive pain management, aligning with goals of faster recovery and minimizing opioid use in oral surgery.